EVALUATION OF QUALITY INDICATORS OF DOUBLE-LAYER POROUS KNITTED FABRICS - O`ralov Lazizbek Soyibnazar o`g`li; Jo`rabayev Abdurashid To`ramirzayevich (Journals Park Publishing, 2022)
In this paper, in order to evaluate the quality indicators of the two-layer porous knitted fabric, 5 samples were knitted on Mayer&Cie double circular needle knitting machine, and as a result of comparing the comparative histogram of the quality indicators, the best sample was was selected and recommended for production.
Keywords: Property, complex, triangle, polygon, porous, quality, area, angle, comparative, diagram, index.